CONTROVERSY OF THE ELECTRONIC INFORMATION TECHNOLOGY LAW - Syafri Madyo Utomo; Esmenov Kiromaciva (Faculty of Law, Khairun University, 2022)
Laws or legislation are laws that have been passed by the legislature or other elements of resistance. Before being enacted, the law is referred to as a draft law. Laws serve to be used as authority, to regulate, to recommend, to provide funds, to punish, to grant, to declare, or to restrict something. A law is usually proposed by members of the legislature, for example members of the DPR, the executive, for example the president, and then discussed among members of the legislature. Laws are often amended before they are passed or may also be rejected. Law is seen as one of the three main functions of government which derives from the doctrine of separation of powers. The group that has the formal power to make legislation is known as legislators who make laws, while the judiciary of the government has the formal power to interpret legislation, and the executive branch of government can only act within the limits of the powers set by statutory law.